A descriptive study on understanding if lockdown restrictions eroded the in-store experience - Thovhakale, Lufuno (The IIE, 2022)
There exists a large body of literature focused on the realm of retail that underscores retail store attributes as the primary determining factor that dictates store choice and purchase behaviour (Paulins & Geistfeld, 2003: 371; Terblanche & Boshoff, 2004:3; Leszczyc & Timmermans, 2001:493). The literature further highlights the array of merchandise and its subsequent assortment as the components of the conventional retail marketing mix (Terblanche & Boshoff, 2004:3-4) Although true, Sands, Oppewal and Beverland (2009:386) bring to attention the heightened significance for in-store experiences to fall within the marketing mix and the continuous pressure around the need to develop novel and innovative lenses to view these experiences. The authors relate this need to how the holistic understanding of in-store experiences and its integration into the marketing mix carries the potential for retail stores to differentiate themselves from their competitors, and adapt to ever changing and accelerating environmental circumstances (Sands et al, 2009:394)- as seen with the state of the environment during the COVID-19 pandemic. The purpose of this research was to understand the importance of the in-store experience and if its reduced presence affects consumers overall experience and thus their perception of H&M and consequent behaviour and loyalty towards the brand. The study followed a qualitative approach that favoured a hermeneutic phenomenological design, in order to develop an in-depth ‘human’ based understanding around the phenomenon. The study additionally made use of non-probability sampling, where 9 South African Generation Z (Gen Z) participants who had visited an H&M store during the nationwide lockdown period were purposively selected as the individuals to participate in the collection of data. The data collection was implemented as an online questionnaire, whose results were then interpreted by way of thematic analysis. The key findings as a result of the data analysis allowed the researcher to unearth four (4) themes that largely affected participants’ in-store experience, namely, style which indicated how the type of clothing offered by H&M sits at the centre of whether and why consumers identify as casual shoppers or loyal consumers. Internal store features such as the organisation of the store’s layout and on-floor staff personnel, follow as another theme that effects the experience of a brand, and lastly, product performance and consumption habits were the last two themes found to impact consumer behaviour. The above findings led to the understanding that without the inclusion of all the factors that fall within each theme in a manner that meets the participants’ needs, there exists no real intention regarding purchase as participants are unable to maximise the utility of procuring products from H&M. Hence, the study’s focus on the in-store experience as a whole.
The case of H&M
Keywords: Lockdown; Retail; Customer behaviour; Buying patterns